Ionic Liquid with a Dual‐Redox Couple for Efficient Dye‐Sensitized Solar Cells. Issue 1 (12th December 2013) - Chu, Te‐Chun; Lin, Ryan Yeh‐Yung; Lee, Chuan‐Pei; Hsu, Chih‐Yu; Shih, Pei‐Chieh; Lin, Ray; Li, Sie‐Rong; Sun, Shin‐Sheng; Lin, Jiann T.; Vittal, R.; Ho, Kuo‐Chuan
Abstract A new type of ionic liquid that contains a nitroxide radical (NO.) and iodide as two redox couples, JC‐IL, has been successfully synthesized for high‐performance dye‐sensitized solar cells (DSSCs). Both of the redox couples exhibit distinct redox potentials and attractive electrochemical characteristics. The UV/Vis absorption spectra of JC‐IL shows a low‐intensity peak compared to the strong absorption of I2 in the wavelength region of 350–500 nm. The high open‐circuit voltage of DSSCs with JC‐IL is over 850 mV, which is approximately 150 mV higher than that of the DSSCs with a standard iodide electrolyte. The dramatic increase in the standard heterogeneous electron‐transfer rate constant leads to an increase in the short‐circuit current for JC‐IL compared to that of 2, 2, 6, 6‐tetramethylpiperidin‐N‐oxyl (TEMPO). DSSCs with the JC‐IL electrolyte show promising cell efficiencies if coupled with dyes CR147 (8.12 %) or D149 (6.76 %). The efficiencies of the DSSCs based on the JC‐IL electrolyte are higher than those of DSSCs based on either TEMPO electrolyte or standard iodide electrolyte alone.